Arqueologia da forma: Herberto Helder, Nuno Ramos e Paulo Henriques Britto - Carolina Anglada de Rezende (2018)
The purpose of this research is to perform an archeology of form, problematizing the terms involved, archeology and form, in the sense that it is necessary to understand epistemologically the method and the object, which in perspective with the contemporary, address us not only in theoretical and critical discourse but, above all, through artistic works. For this reason, we worked on the relationship between the arkh and the human sciences, developed in the work of important thinkers such as Michel Foucault, Jacques Derrida and Philippe Lacoue-Labarthe, in order to reflect on the meaning of its recurrence in the twentieth century and the pertinence of such a gesture until this day. As the notion of form, object of this research, responds by the category of concept, we propose a discussion about conceptual thinking considering ideas such as Hans Blumenbergs nonconceptuality, and Benjamins thought by images, both rigorous fronts of the analytic exercise in union with the poetic. From these questions, an archeology of the form is traced as a history of a history of the moments in which this notion enabled the thought to address aspects of visibility, appearance, performance, and achievement. With this archeology, the objective is to perceive the echoes, the disagreements and the contrasts between these different ways of conceiving the formal dimension and the works of three contemporary writers of Portuguese language, Herberto Helder, Nuno Ramos and Paulo Henriques Britto. For the former, the metamorphosis is more important, the processes of transformation and becoming, worked not only thematically but interwined with the very notion of work, while Nuno Ramos enters the universe of formation, creating objects to observe how matter is conceived and related to other matters. The comparison of such authors in the same scenario, becomes more complex when we deal with the poetry of Paulo Henriques Britto, for whom the form is constructed in an intense confrontation with the limits of the language, being expressed in compositions of fixed metrics. Therefore, we consider not only form, but also its inflections such as formless, performance, and metamorphosis, in order to think about how these terms interrogate us and pose questions for our present time.